2-Methyl-6-(4-aminophenyl)-4,5-dihydro-3(2H)-pyridazinone Synthon for Some New Annelated 1,2,3-Selena/Thiadiazoles and 2H-Diazaphospholes with Anticipated Biological Activity and Quantum Chemical Calculations - El-Shamy, I E; Hleli, E; El-Hashash, M A; Kelnar, I; Abdel-Mohsen, A M (Molecules (Basel, Switzerland), 2023)
A convenient and efficient synthetic protocol for the new selenadiazole. Thiadiazole and diazaphosphole derivatives incorporating a pyridazine moiety originating from 4-(4-aminophenyl)-4-oxobutanoic acid (1) were described. All newly synthesized compounds were evaluated for their antimicrobial activity using the disk diffusion method, and their cytotoxicity was evaluated against brine shrimp lethality bioassay. Using density functional theory (DFT), the frontier molecular orbital (FMO) and molecular electrostatic potential (MEPS) were studied to estimate the chemical reactivity and kinetic stability of each structure. Therefore, global descriptor parameters like electronegativity (χ), chemical hardness (η), and global softness (σ) were calculated. Consequently, the attained results were compared with the experimental data of the biological activity of the studied structures.
Keywords: thiadiazole; antimicrobial activity; pyridazinone; DFT calculations; cytotoxicity; selenadiazole